2019
DOI: 10.1299/jbse.19-00034
|View full text |Cite
|
Sign up to set email alerts
|

Electromyostimulation influences the mechanical properties and microarchitectures of bones beyond the stimulation site

Abstract: Electromyostimulation is a nonpharmacological prevention method for osteoporosis that is safe and feasible for the elderly and people with physical disabilities. Our previous study demonstrated that random pulse train (RdPT) electromyostimulation of rat quadriceps induces an increase in the mechanical properties of the contralateral unstimulated femoral neck. However, the efficacy of this stimulation on other untested bones is still unclear. The objective of this research is to investigate the response of prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Bone cells may not be desensitized (Saxon et al, 2005) because of the forementioned randomness. We previously showed that RdPT ES to the quadriceps muscle can improve the mechanical properties of bone in a rat model more effectively than the control and PrPT ES (Tanaka et al, 2017 andLimbong et al, 2019). Interestingly, this effect of RdPT ES was not accompanied by an increase in the BMD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bone cells may not be desensitized (Saxon et al, 2005) because of the forementioned randomness. We previously showed that RdPT ES to the quadriceps muscle can improve the mechanical properties of bone in a rat model more effectively than the control and PrPT ES (Tanaka et al, 2017 andLimbong et al, 2019). Interestingly, this effect of RdPT ES was not accompanied by an increase in the BMD.…”
Section: Discussionmentioning
confidence: 94%
“…The electrodes were placed in the wells of the control group without ES. ES was applied to the cells for 3 min/day for the first three consecutive days (days 1-3) based on the stimulation regimen used in our previous studies (Takimoto and Tanaka, 2010;Limbong et al, 2019).…”
Section: Electrical Stimulation (Es)mentioning
confidence: 99%